Flexibility and strength training in asthma: A pilot study. (2nd December 2018) - Olenich, Sara; Waterworth, Graeme; Badger, Gary J.; Levy, Bruce; Israel, Elliot; Langevin, Helene M.
ABSTRACT: Objective : Although less is known about musculoskeletal factors that may contribute to asthma symptoms, body-based treatments addressing movement restrictions of the chest and shoulders may be a useful adjunct to asthma pharmacotherapy. In this pilot study, we compared asthma symptoms, pulmonary function tests, and medication use before and after a course of resistance flexibility and strength training (RFST) treatments in human subjects with asthma. Methods : Patients with asthma ( n = 10; mean age 23 years) completed questionnaires (Asthma Control Questionnaire (ACQ), Asthma Quality of Life Questionnaire (AQLQ), Asthma Control Test (ACT)), spirometry, chest wall excursion, and shoulder range of motion (ROM) before and after a series of four RFST treatments over 47 ± 21 days. Each treatment consisted of a one-hour session involving eccentric stretching of the arm, shoulder, and chest while lying in a supine position. Results : Significant clinical improvement was observed for mean ACQ scores from pre- to post-treatment (mean decrease 0.73, 95% CI 0.26–1.09, Cohen d = 2.25, p =.0014). No significant improvement was observed in the ACT, AQLQ, or spirometry, although inhaler use decreased for half of the subjects and did not change for the remaining subjects (i.e. none increased). Chest wall excursion and all ROM tests trended toward improvement, but was only statistically significant ( p <.05) for the arm raise in the frontal plane. Conclusion : RFST may be a beneficial, nonpharmacological method to decrease asthma symptoms. Future studies should be conducted involving a larger sample size, longer intervention time, control group, and blood collection to test inflammatory mediators.